Pancreatic Hemangioma Suspected of Neuroendocrine Tumor - Mo Ah Jeong; Jun Kyu Lee; Ji Hyung Nam; Dong Kee Jang; Yun Jeong Lim; Jeong-Ju Lee; Eo-Jin Kim (The Korean Journal of Gastroenterology, 2020)
Adult pancreatic hemangioma is an extremely rare disease, with only 22 cases reported since 1939. Pancreatic hemangioma has no specific symptoms, diagnostic imaging, or laboratory findings, making it difficult to be clinically suspected and diagnosed. The majority are confirmed after surgery. In this report, a 61-year-old woman presented with melena and showed multiple small hyper-vascular lesions in the pancreas. A pancreatic neuroendocrine tumor was suspected, and the patient underwent a distal pancreatectomy. The pathology examination and immunohistochemical study revealed a pancreatic hemangioma.